1996
DOI: 10.1016/s0009-9236(96)90148-4
|View full text |Cite
|
Sign up to set email alerts
|

The cytochrome P450 2D6 (CYP2D6) enzyme polymorphism: Screening costs and influence on clinical outcomes in psychiatry*

Abstract: Screening psychiatric patients for CYP2D6 expression may distinguish metabolic-based therapeutic problems from drug sensitivity caused by other mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(77 citation statements)
references
References 36 publications
1
73
0
3
Order By: Relevance
“…The newer CYP450 array and assay was not used in this research so that consistency could be maintained throughout the evaluation process. Considering the magnitude of the variation that exists in the CYP2D6 gene, the high-throughput, informationrich oligonucleotide microarray is a very practical solution to the more traditional genotyping approaches that typically assess one polymorphism at a time (e.g., restriction fragment length polymorphism analysis, AS-PCR, TaqMan ® ) (2,4 ). To acquire the same information obtainable from a single GeneChip assay requires far more work and labor and remains too slow and/or expensive to justify in a routine clinical environment.…”
Section: Cyp2d6 Allele Frequencies In Us Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The newer CYP450 array and assay was not used in this research so that consistency could be maintained throughout the evaluation process. Considering the magnitude of the variation that exists in the CYP2D6 gene, the high-throughput, informationrich oligonucleotide microarray is a very practical solution to the more traditional genotyping approaches that typically assess one polymorphism at a time (e.g., restriction fragment length polymorphism analysis, AS-PCR, TaqMan ® ) (2,4 ). To acquire the same information obtainable from a single GeneChip assay requires far more work and labor and remains too slow and/or expensive to justify in a routine clinical environment.…”
Section: Cyp2d6 Allele Frequencies In Us Populationmentioning
confidence: 99%
“…Recent results from several laboratories have demonstrated that a limited CYP2D6 allele set may predict the vast majority of Caucasian individuals lacking CYP2D6 enzyme activity with close to 100% accuracy (2)(3)(4)(5)(6)(7)(8). As more CYP2D6 null and reduced activity alleles have been discovered in various populations, the ability to account for more subtle variations in CYP2D6 enzyme activity has improved.…”
mentioning
confidence: 99%
“…36 Furthermore, a prospective 1-year clinical study of 100 psychiatric inpatients suggested a trend toward longer duration of hospital stay and higher treatment costs in UMs and PMs of CYP2D6. 37 In conclusion, for treatment with antidepressants, there is extended evidence mainly for CYP2D6 and, to a lower extent, for CYP2C19 polymorphisms affecting pharmacokinetics of several antidepressants and possibly affecting therapeutic outcome and adverse drug effects. The usefulness of genotyping procedures in depressed patients, however, has not been confirmed in prospective clinical trials; therefore, currently this approach is limited to a few enthusiastic hospitals, such as the Mayo Clinic, and to some patients with adverse or no therapeutic effects.…”
mentioning
confidence: 99%
“…[16][17][18] A genomic variation will have therapeutic relevance when ALL the following criteria are met:…”
Section: Therapeutic and Economic Issues Surrounding Routine Pharmacomentioning
confidence: 99%
“…Realistically, genomic testing by most clinical labs is not likely to fall much below about $50 per test in the immediate future, and is more likely to remain near $100 or so per sample in many clinical labs. The current trend is to test for multiple variations in a given gene and multiple genes that can affect therapeutic response, 7,8,16 and this trend adds to the cost of genetic testing even as testing methods improve. Thus, the actual clinical cost of genomic testing will probably remain within a range of between $50 000-$250 000 per 1000 samples tested, with the actual cost hovering close to $100 000-$150 000 per 1000 samples tested over the short term in spite of improved efficiencies in genetic testing methodologies.…”
Section: Therapeutic and Economic Issues Surrounding Routine Pharmacomentioning
confidence: 99%